Pengaruh Penambahan Saccharomyces cerevisiae pada Pengolahan Tepung Berbagai Jenis Telur Terhadap Mutu Tepung - Ermina Syainah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2012)
White-egg flour is refined food product, it’s make from white-egg, because oats has high price and for minimize about oats import, so making flour has combine with duck egg and chicken egg and ras chicken egg. White-egg flour has made from material local basic with 2 type egg for develop utilization egg waste and for chance to develop entrepreneurship. This research implemented at Laboratory Technology Food Medical of Polytechnic Nutrient Banjarmasin, Laboratory Microbiology and Analysis Material/Product Industry Agriculture Faculty Unlam Banjarbaru. It’s call with Plan Complete Random (RAL). Observation for nutrient substance content, such as test about protein content and water content. Result about research is for analysis nutrient content give best result about the type duck egg than chicken and ras chicken egg. For analysis protein content, duck egg 86,7319%, chicken egg 86,4680%, ras chicken egg 85,5791% and for water content has the best to ras chicken egg around 8,7206% and duck egg 8,1789% and chicken egg 7,9552%